Hi, my friend gave me this to solve Care to help me here, this can't be right? Given: a=b aČ=a.b aČ-bČ=ab-bČ (a+b)(a-b)=b(a-b) (a+b)=b a+a=a 2a=a 2=1 Am I right in saying this does not compute? (a+b)(a-b)=b(a-b)
Follow Math Help Forum on Facebook and Google+
the problem is the cancellation, since a=b, a-b is zero and you cant divide (cancel) by zero
Originally Posted by emathinstruction the problem is the cancellation, since a=b, a-b is zero and you cant divide (cancel) by zero I thought this wase too minor, nevermind, I shall pass the news along, just wanted to check
View Tag Cloud